DEATH IN 2020 AND A COVID-19 GREAT EPIDEMIC: AN ISLAMIC ANALYSIS - Hossain, Md. Kohinoor (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
Only love to almighty Allah is the greatest love. From ages to ages, Allah has sent his messengers to preach only love to Him. Many destructions, disruptions, and explosions have occurred in this world. This paper tries to explore the causes of the great disasters in the world. The global people when they lead an invalid way, there occurs a terrible crisis. None of the worlds saves it. Only Allah can save global people. Today, the present world is full of share-ism, idolatry-ism, usury-ism, zakat-free-ism, killing-ism, injustice-ism, and inhumanity-ism. They practice about Gods and Goddesses. They believe that the sun, the moon, the stars, the trees, the stone, the angels, the jinn, and other animals can reach Allah. They are the dearest persons who are God, Gods, Goddess, and Goddesses related. Above eleven million people think and say that there is no creator of the universe. It is operating as automated. Marriages and sexism are human to animal. They practice as same-sex, polygamy, polygyny, and polyandry. Most of the global people pray to Materials, Death Guru, God, Gods, Goddess, Goddesses, Peer, Saai, Baba, Abba, Dihi Baba, Langta Baba, Khaja Baba, Joy Guru, Joy Chisty, Joy Baba Hydery, Joy Maa Kali, Maa Durga, Moorshid Kibla, Baba Haque Bhandary, Joy Ganesh Pagla, Joy Deawan Baggi, Joy Chandrapa, Joy Sureshwaree, Fooltali Kebla, Sharshina Kebla, Foorfoora Kebla, Joy Ganapati, Joy Krishnan, Joy Hari, Joy Bhagaban and Mazzarians. The new religions have preached in the world such as Baha’i, Kadyany, Khaljee, Din-E-Elahi, Brahma, and Humanism. The world is full of Shirkism, Moonafikism, Goboatism, Bohtanism, Mooshrikiaism, Oathlessism, and Khianotkariism. In the past, undetermined civilizations have vanished but none can save civilization. This Covid-19 great destruction is human-made. It is from climate change that comes to the global people as a great curse.